The Influence of Motivation and Workload on Job Satisfaction as Customer Service at PT Telkom Witel North Surabaya - Kharisma, Annas; Kurniawati, Masmira (Universitas Proklamasi 45, 2024)
PT Telekomunikasi Indonesia (PT Telkom) will carry out an organizational transformation known as the Five Bold Moves. The purpose of this research is to analyze the relationship between employee motivation and workload on customer service satisfaction at PT Telkom Witel North Surabaya. This study employs a quantitative strategy of the explanatory kind. Multiple linear regression analysis is used here. According to the findings, intrinsic motivation significantly affects occupational fulfillment. In other words, employee happiness rises in tandem with the quality of the company's incentives. Workload also affects morale in the workplace. So, the more responsibility an employee is given, the happier they will be in their employment. Then, both intrinsic motivation and a heavy workload boost happiness on the job. That is to say, job satisfaction increases with both intrinsic desire and a reasonable amount of effort. Given the significance of the study's independent variables in explaining workers' levels of contentment on the job, it is hoped that the findings presented here will serve as a springboard for further investigation into these and related issues by researchers in the future.